Integrated Water Management for sustainable agricultural production - Singh, Raman Jeet; Sharma, N. K.; Singh, Surender (Indian Farming, 2015)
More research needs to be done to make sure that management of water and other resources is based on sound science and engineering. Much greater local, national, and international efforts,cooperation, and expenditures are needed to meet future food and water requirements in sustainable, peaceful, and environmentally responsible ways.